Encyclopedia of Life Sciences 2017
DOI: 10.1002/9780470015902.a0020097.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Endopolyploidy in Plants

Abstract: Endopolyploidy is a general term describing the multiplication of nuclear DNA within the cell. In plants, this takes place via several mechanisms but mainly through the process of endoreduplication. Endoreduplication involves the replication of chromosomal deoxyribonucleic acid (DNA) without intervening mitoses and no obvious chromatin condensation/decondensation, with chromatids staying united either at the centromere or rarely, along their entire length. The occurrence of this form of endopolyploidy is uneve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Microscopy observations of endoreduplicated chromosomes in plants have been more limited, but full or partial polyteny has been described in suspensor and tapetum cells, xylem cells, and trichomes (Nagl, 1969;Carvalheira, 2000;Sugimoto-Shirasu and Roberts, 2003). Endoreduplicated plant chromosomes have been observed to be incompletely aligned or partially polytene, and the degree of chromatid synapsis tends to decrease as ploidy increases (Matzke et al, 2005;Schubert et al, 2006Schubert et al, , 2012Leitch and Dodsworth, 2017). The degree of polyteny can also be cell type specific: Analysis of fluorescent centromere markers suggested that endoreduplicated Arabidopsis root cells were completely polytene at the centromere, whereas chromosomes in endoreduplicated leaf pavement cells were more dissociated (Fang and Spector, 2005).…”
Section: Distinctions Between Endopolyploidy and Wgm Ploidy Changementioning
confidence: 99%
“…Microscopy observations of endoreduplicated chromosomes in plants have been more limited, but full or partial polyteny has been described in suspensor and tapetum cells, xylem cells, and trichomes (Nagl, 1969;Carvalheira, 2000;Sugimoto-Shirasu and Roberts, 2003). Endoreduplicated plant chromosomes have been observed to be incompletely aligned or partially polytene, and the degree of chromatid synapsis tends to decrease as ploidy increases (Matzke et al, 2005;Schubert et al, 2006Schubert et al, , 2012Leitch and Dodsworth, 2017). The degree of polyteny can also be cell type specific: Analysis of fluorescent centromere markers suggested that endoreduplicated Arabidopsis root cells were completely polytene at the centromere, whereas chromosomes in endoreduplicated leaf pavement cells were more dissociated (Fang and Spector, 2005).…”
Section: Distinctions Between Endopolyploidy and Wgm Ploidy Changementioning
confidence: 99%
“…() and Brown et al . (), respectively), cells only replicate specific parts of chromosomal DNA, resulting in nuclei with (substantially) a less than two‐fold increase in DNA content (Leitch & Dodsworth, ). This phenomenon has been identified in representatives of all orchid subfamilies except the Apostasioideae (Trávníček et al ., ) and exhibits clade‐specific, and therefore phylogenetically constrained, behaviour (Bateman et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Barkla et al. (2018) pointed out that “highly metabolically active cells appear to have the highest levels of endopolyploidy, as it has been demonstrated in the endosperm and suspensor cells of the seeds of Arum maculatum and Phaseolus coccineus (24,567 and 8,192C, respectively; Leitch and Dodsworth, 2017 )”. Despite a majority of tissues within Arabidopsis endoreduplicate at a basal level ( Buchanan et al., 2000 ), it is important to keep in mind that endopolyploidy-associated growth is sometimes confined to specialized cell types or tissues that perform specific biological functions ( e.g.…”
Section: Resultsmentioning
confidence: 98%